Frame approach to motivation of proper nouns - Зимовець, Галина Вікторівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The author argues for frame approach to the analysis of proper names. It relies on the action-based conception of language, according to which meaning of words is formed in communication on the ground of subjective representations of entities of objective reality. Within this approach, both linguistic and encyclopedic knowledge are taken under account. Therefore, it is important to consider all set of perceptions and ideas an individual has about a referent. The nominator selects a name based on a specific motivation that sometimes remains vague for a recipient. 'Internal form' of the word relies on a range of different features that the nominator ascribes to a respective object. Originally, proper nouns also have a transparent motivation, which is clear for a nominator. This motivation depicts relevant features of an object of nomination. From perspective of this theoretical model, the author has analyzed motivation of Ukrainian business names that allowed defining the structure of the business activity frame that is activated in the process of companies and organizations naming. The main slots of this frame include 1) object of an activity; 2) recipient of an activity, i.e. a potential client or a partner; 3) addresser, i.e. an actor, an agent who produces something or delivers services; 4) place of activity in a broad sense, including type of premises and geographical location; 5) organizational form. There are additional slots of the frame that are integrated into slots of an addresser and a recipient – 6) evaluation and values (pragma-axiological motivation), and 7) individual and collective symbols (symbolical motivation). The last two slots are based on an intensional meaning of motivators. The frame highlights stereotype understanding of the situation of interpersonal interaction in public and economic sphere.